Agile IT Governance for Sustainable Digital Transformation in Universities - Batmetan, Johan Reimon (International Journal of Information Technology and Education, 2025)
The increasing demand for sustainable digital transformation in higher education requires governance models that are adaptive, flexible, and resilient. Traditional IT governance frameworks often lack the agility to respond to rapidly changing technological, institutional, and societal needs. This study explores the application of Agile IT Governance as a strategic approach to support sustainable digital transformation in universities. Using a mixed-methods design, the research combines a systematic literature review with empirical insights from case studies conducted in Indonesian universities. The findings reveal that Agile IT Governance enables faster decision-making, promotes stakeholder collaboration, and strengthens the alignment between institutional objectives and technological innovations. Furthermore, the study highlights the critical enablers of successful implementation, including leadership commitment, organizational culture, digital competencies, and adaptive policy frameworks. This research contributes to the theoretical advancement of IT governance by integrating agile principles into the context of higher education, while also providing practical recommendations for policymakers and university leaders seeking to ensure long-term digital sustainability.